Accuracy of alcohol and breast cancer risk information on Drinkaware's website. (12th February 2018) - Larsen, John; Wallace, Paul; Sim, Fiona; Chick, Jonathan; Jarvis, Sarah; Lidington, Iona; Neidle, Stephen; Ogden, Graham; Owens, Lynn
Abstract: A recent paper in Drug and Alcohol Review analysed the information on cancer disseminated by 27 alcohol industry funded organisations. The independent UK alcohol education charity Drinkaware was among the organisations whose information was studied, and based on the analysis claims were made of misrepresentation of evidence about the alcohol‐related risk of cancer and alcohol industry influence. This commentary challenges the validity of these findings in respect to the evidence relating to the Drinkaware information, as the analysis is found to be misrepresenting the information by both disregarding the wider information content provided and the order and prominence with which alcohol‐related cancer risk is presented. Furthermore, it is argued that the public has a right to be provided with relevant evidence‐based information about cancer risk. It is critical that Drinkaware's important public health function is not compromised by unjustified allegations of inaccuracy and by unwarranted attacks on its independence and integrity.